Giant Right Intrathoracic Myxoid Fusocellular Lipoma - Petre V. H. Botianu; Anda Mihaela Cerghizan; Alexandru M. Botianu (Case Reports in Pulmonology)
Intrathoracic lipomas are rare benign tumors; their behavior is not completely clear and their surgical removal may be challenging. We report a case of a giant right intrathoracic myxoid fusocellular lipoma compressing the lung, tracheobronchial tree, and esophagus which was removed through a posterolateral thoracotomy. Complete removal resulted in resolution of the chest pain and improvement of the dyspnea, with no recurrence at 4-year follow-up.